A Snapshot of Female Representation in Twelve Academic Psychiatry Institutions Around the World. (February 2022) - Kenney, Joanne; Ochoa, Susanna; Alnor, Mohamed Abdalhameed; Ben-Azu, Benneth; Diaz-Cutraro, Luciana; Folarin, Royhaan; Hutch, Avril; Luckhoff, Hilmar Klaus; Prokopez, Cintia R.; Rychagov, Nicole; Surajudeen, Bakare; Walsh, Louise; et al.
Highlights: Unequal representation of women exists in psychiatry and neuroscience across countries Data from twelve institutions from Africa, South America, European Community and North America indicate negative correlation between women representation and career stage in academia There are some differences in the degree of leaky pipeline across institutions. Leaky pipeline refers to the attrition of the number of women such that at early career stages, women outnumber men but at senior ranks, men greatly outnumber women. Leaky pipeline may reflect the fact that women leave academia at higher rates than men or/and by women facing significant barriers in attaining academic promotion, the so-called 'bottleneck' effect. Both common and country-specific underlying mechanisms appear to be at the root of unequal representation of women in psychiatry and neuroscience across countries Abstract: The study presented here aims at bringing a global perspective to the phenomenon of unequal representation of females in science by offering empirical data of female representation in neuroscience/schizophrenia academic or clinical departments in several institutions around the world. We took advantage of a budding network of scientists and colleagues from different countries to bring the data together. The data presented are related to sex, that is the biological distinction between males and females, based on genetics and reproductive anatomy, while gender, considered a cultural concept was harder to determine. We report data from two clinical/academic departments in Nigeria, Africa; 2 clinical/academic departments from Sudan, Africa; 1 clinical/academic department from South Africa, Africa; 3 academic institutions from Ireland, Europe; 1 clinical/academic institution from Spain, Europe; 2 academic institutions from Buenos Aires University, Argentina; and the Psychiatry Departments at Harvard Medical School, Boston, USA.